Determination of chemical elements in magnesium-based materials by neutron activation analysis - Caio Almeida Justino Silva; Lilian Ninoska Muriel Braguin; Jesualdo Luiz Rossi; Isolda Costa; Mitiko Saiki (Brazilian Journal of Radiation Sciences, 2021)
Over the last decades there was an increasing interest in using magnesium alloys for medical applications due to their biodegradability in the human body, providing a temporary mechanical support and corroding completely after the tissue healing. Although magnesium is a non-toxic element, it is of great importance to evaluate the element concentration, as well as the impurities present in both, pure magnesium and magnesium alloys, as the AZ31. The purpose of this study was to analyze the element composition of these materials using the method of neutron activation analysis (NAA). Standard Reference Materials (SRMs) acquired from National Institute of Standards and Technology (NIST) were analyzed for analytical quality control. Short and long term irradiations were carried out at the IEA-R1 nuclear research reactor and gamma-ray activities induced to the samples and element standard were measured using HPGe detector coupled to a Digital Spectrum Analyzer. The radioisotopes were identified by gamma ray energies and half-life. Concentrations of the elements As, Cr, Cd, Co, Fe, In, La, Mg, Mn, Mo, Na, Sb, V, W and Zn were determined in pure magnesium sample and the Al, As, La, Mg, Mn, Na, Sb and Zn in the AZ31 alloy, calculated by comparative method. The SRMs were analyzed by applying the same experimental conditions used for magnesium-based materials and their results presented good accuracy and precision. Thus, from the measurements obtained in this study it can be concluded that NAA is a suitable method for element determinations in magnesium-based materials providing reliable results.